Biological significance of C-reactive protein, the ancient acute phase functionary - Bhattacharya, Shelley; Munshi, Chayan (Frontiers in Immunology, 2023)
C-reactive protein (CRP) is one of the major members of the family of acute phase proteins (APP). Interest in this CRP was the result of a seminal discovery of its pattern of response to pneumococcal infection in humans. CRP has the unique property of reacting with phosphocholine-containing substances, such as pneumococcal C-polysaccharide, in the presence of Ca2+. The attention to the origin of CRP and its multifunctionality has gripped researchers for several decades. The reason can be traced to the integrated evolution of CRP in the animal kingdom. CRP has been unequivocally listed as a prime tag of infectious and inflammatory diseases including autoimmune diseases. The first occurrence of CRP in the evolutionary ladder appeared in arthropods followed by molluscs and much later in the chordates. The biological significance of CRP has been established in the animal kingdom starting from invertebrates. Interestingly, the site of synthesis of CRP is mainly liver in vertebrates, while in the invertebrates it is located in diverse tissues. CRP is a multifunctional player in the scenario of innate immunity. CRP acts as an opsonin in the area of complement activation and phagocytosis. Interestingly, CRP upregulates and downregulates both cytokine production and chemotaxis. Considering various studies of CRP in humans and sub-human animals, it has been logically proposed that CRP plays a common role in animals. CRP also interacts with Fcγ receptors and triggers inflammatory response of macrophages. CRP in other animals such as primates, fish, echinoderms, arthropods and molluscs, has also been studied in some detail which establishes the evolutionary significance of CRP. In mammals, the increase in CRP levels is an induced response to inflammation or trauma; interestingly, in arthropods and molluscs, CRP is constitutively expressed and represents a major component of their hemolymph. Investigations on the primary structure of CRP from various species revealed the overall relatedness between vertebrate and invertebrate CRP. Invertebrates lack an acquired immune response; they are therefore dependent on the multifunctional role of CRP leading to evolutionary success of the invertebrate phyla.